New species of the genus Troglophilus Krauss, 1879 (Orthoptera: Rhaphidophoridae) from Western and Southern Anatolian caves, Turkey - Taylan, Mehmet Sait; Russo, Claudio Di; Cobolli, Marina; Rampini, Mauro (Zootaxa, 2012)
In this paper four new species of Troglophilus Krauss, 1879 cave crickets from Southern and Western Anatolia are described (T. alanyaensis, T. fethiyensis, T. ozeli and T. ferzenensis). Considering the other five species already documented from the area, there is now a total of 9 recorded species of Troglophilus that currently inhabit the caves and epigean habitats of Turkey. The occurrence of two new species in the western Aegean region of the Anatolia (Troglophilus fethiyensis sp. nov. and T. ozeli sp. nov. from Mugla and Havran provinces respectively) allowed us to improve considerevely the knowledgements on their geographic ditribution in Turkey, until now limited to the Southern Anatolia and a to a little enclave of Pontic region. The new species are all morphologically homogeneous, showing a clear affinity with the other Anatolian species T. adamovici Us, 1974; T. gajaci Us, 1974; T. escalerai Bolivar, 1899 and T. bicakcii Rampini & Di Russo, 2003 from Southern Taurus caves. The best character that permits to distinguish these groups is the ovipositor shape. Of particular interest is the finding of the new species T. ferzenensis sp. nov. in the Ferzene cave. This species, synoptic with T. adamovici, although morphologically similar to T. escalerai, differs from all the known Turkish species in the different spinulation of the legs, resulting close to the Aegean species T. spinulosus Chopard, 1921 from Crete and T. marinae Rampini & Di Russo, 2003 from Santorini.